Shame and Philosophy - Hutchinson, P. author. aut Link
IX, 190 p.
Keywords: Engaging with current research in the philosophy of emotions, both analytic and continental, the author argues that reductionist accounts of emotions leave us in a state of poverty regarding our understanding of our world and of ourselves.